TERMS OF SELECTION STRATEGIES SEARCH ALGORITHM POINT WITH CHARACTERISTIC SIGNS INITIAL INTERVAL UNCERTAINTY - Alipov, N. V.; Khil, M. I.; Gusiatin, M. V. (Radio Electronics, Computer Science, Control, 2008)
Agreed designing of information system for forming stock of orders according to market requirement is proposed in this article. It allows to improve managerial decision’s quality and increase profitable part of company’s budget. The procedure of marketing parameters’ complex estimation and projection of object’s characteristic to the value of corresponding scales is viewed (application of different scales according to the solving problem’s type is described). Methods for solving integer-valued linear programming’s problems with use binary variables are given, definition of a problem about rucksack and forming portfolio is considered.